2020
DOI: 10.14217/501dd683-en
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Effects of the COVID-19 Pandemic on Medical Supply Chains in Commonwealth Countries

Abstract: This study analyses the supply chains for medical goods across the Commonwealth countries. It assesses trade flows related to the health sector and, more specifically, import and export data for essential COVID-19 medical supplies. It also explores supply chain disruptions (trade interruptions, changes in consumption and tariffs related to imports) caused in the wake of COVID-19. Based on the analysis and key findings, it proposes policy changes and recommendations to increase the resilience of these supply ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The COVID-19 pandemic has had a direct impact on the medication supply worldwide. 18 Since Nakkasah was under complete lockdown, there was a reduced supply of medications for other conditions, and this could have also contributed to the worsening of comorbid conditions, as highlighted by one of our study participants.…”
Section: Discussionmentioning
confidence: 93%
“…The COVID-19 pandemic has had a direct impact on the medication supply worldwide. 18 Since Nakkasah was under complete lockdown, there was a reduced supply of medications for other conditions, and this could have also contributed to the worsening of comorbid conditions, as highlighted by one of our study participants.…”
Section: Discussionmentioning
confidence: 93%
“…Meanwhile, the EU's weaker domain was PPP. Gopalakrishnan et al (2020) demonstrated that developed countries monopolize the production of high-tech medical equipment, whereas developing countries, such as China, conquer the PPP market. Medical supply exports among Commonwealth countries are dominated by developed countries, whereas developing countries remain the major importers.…”
Section: Literature Reviewmentioning
confidence: 99%